Coffee Value Chain Survey in Ethiopia: Producer/Household Survey - International Food Policy Research Institute; Ethiopian Development Research Institute (International Food Policy Research Institute, 2020)
The coffee producer survey was conducted to study the coffee value chains in order to make recommendations to policymakers on how to improve the value chain to the benefit of farmers. The data collected in this survey helps to understand how the coffee value chains are transforming in terms of quality and demand of coffee, adoption of modern inputs in coffee farming, and farmers' access to input and services.